TERRESTRIAL LASER SCANNER FOR METRIC EXTRACTION IN EUCALYPTUS UNDER DIFFERENT IMPLANTATION SYSTEMS - Ruza, Marieli Sabrina; Dalla Corte, Ana Paula; Angelo, Alessandro Camargo; Sanquetta, Carlos Roberto; Pesck, Vagner Alex (Floresta, 2021)
This study evaluates the influence of the cropping system in the extraction of Eucalyptus benthamii metrics by terrestrial laser scanner (TLS) and by traditional inventory. The hypothesis is that the extraction methods do not differ significantly from each other. The study area consists of a conventional planting system under 3 x 2 m spacing, and a CFI (crop-forest integration) system under 14 x 2 m spacing. To obtain the variables DBH (diameter at 1.3 m aboveground) and total height (H), we used a traditional inventory and collected data with TLS. For point cloud processing, we manually extracted the metrics DBH and H by simple scanning. We estimated total volume (V) by a fitted equation that matches the characteristics of the study area. To estimate above-ground biomass (AGB), we fitted models based on AGB data provided by the NITA project and by BIOFIX. Better visualization of trees in the CFI system facilitated metric extraction, leading to less data variability. In addition, DBH, V, and AGB values were higher in the CFI system compared to the conventional system. However, when including the number of trees per hectare, the conventional system is more productive. The initial hypothesis was confirmed. Therefore, metric extraction using the traditional inventory and TLS methods did not differ significantly for the two cropping systems considered.